The Objective Vision of Sharia Rules at Modernists: A Critical Original study - Mohammed Zubair Wso Husen; Hasan Khalid Mustafa Mahmod (Zanco Journal of Humanity Sciences)
This Reseach is about the contemporary scholars’ perspectives on the term of purpose and the great objectives of Sharia. The study, therefore, provides an overview for the term of Sharia purposes, contemporary trendies and perspectives towards the concept. The study also investigates the scholars’ views and explains how they have used the principles and values of Sharia for their interests and also how they validated their commitments. The study, similarly, tries to explore the contemporary scholars’ methods and intentions for conducting these commitments. It, furthermore, investigates the scientific mistakes that the trendies committed when they use the objectives of Sharia as a tool for providing evidence.